2017
DOI: 10.1158/0008-5472.can-17-1865
|View full text |Cite
|
Sign up to set email alerts
|

H3B-6527 Is a Potent and Selective Inhibitor of FGFR4 in FGF19-Driven Hepatocellular Carcinoma

Abstract: Activation of the fibroblast growth factor receptor FGFR4 by FGF19 drives hepatocellular carcinoma (HCC), a disease with few, if any, effective treatment options. While a number of pan-FGFR inhibitors are being clinically evaluated, their application to FGF19-driven HCC may be limited by dose-limiting toxicities mediated by FGFR1-3 receptors. To evade the potential limitations of pan-FGFR inhibitors, we generated H3B-6527, a highly selective covalent FGFR4 inhibitor, through structure-guided drug design. Studi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
100
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(101 citation statements)
references
References 58 publications
1
100
0
Order By: Relevance
“…Although multiple pan‐FGFR tyrosine inhibitors have already been evaluated in clinical trials for patients with abnormal FGFR signaling, their toxicity because of their low specificity has limited their use . Recently, selective FGFR4 inhibitors for the treatment of HCC were developed that overcame the shortcomings of pan‐FGFR inhibitors . One of the selective FGFR4 inhibitors, BLU9931, was reported to show remarkable antitumor ability in HCC harboring FGF19 amplification or in HCC overexpressing FGF19 that lacked amplification .…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple pan‐FGFR tyrosine inhibitors have already been evaluated in clinical trials for patients with abnormal FGFR signaling, their toxicity because of their low specificity has limited their use . Recently, selective FGFR4 inhibitors for the treatment of HCC were developed that overcame the shortcomings of pan‐FGFR inhibitors . One of the selective FGFR4 inhibitors, BLU9931, was reported to show remarkable antitumor ability in HCC harboring FGF19 amplification or in HCC overexpressing FGF19 that lacked amplification .…”
Section: Discussionmentioning
confidence: 99%
“…FGF19 amplification is a very appealing therapeutic target with the development of selective inhibitors of its receptor, FGFR4. 30,31 However, FGF19 amplifications were not always associated with its overexpression both in LCCL and HCC tumors. We showed that only LCCL expressing a hepatocyte differentiation program with conserved expression of the FXR transcription factor and of the receptor complex, including FGFR4 and KLB, were sensitive to the FGFR4 inhibitors, which extends other previous findings.…”
Section: Andmentioning
confidence: 95%
“…H3B-6527 is a highly selective and covalent small-molecule inhibitor of FGFR4, which has been reported to be effective in inhibiting cell proliferation in vitro and in xenografts models of hepatocellular carcinoma. 22 Our results indicate that blocking FGFR4 by H3B-6527 could significantly inhibit ESCC cell proliferation in vitro. In additional, we found that FGFR4 blockade attenuated the migration and invasion ability of ESCC cells.…”
Section: Discussionmentioning
confidence: 55%
“…To explore the effects and mechanisms of blocking FGFR4 in ESCC, we selected two cell lines, KYSE150 and KYSE450, with relatively high FGFR4 expression levels for further study. H3B‐6527 is a highly selective and covalent small‐molecule inhibitor of FGFR4, which has been reported to be effective in inhibiting cell proliferation in vitro and in xenografts models of hepatocellular carcinoma . Our results indicate that blocking FGFR4 by H3B‐6527 could significantly inhibit ESCC cell proliferation in vitro.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation